“Qualitative /situational analysis of prevalence and practices to prevent anaemia among Adolescents of Telangana Social Welfare Residential Educational Institutions Society” –Stakeholder-principal (International Journal of Food and Nutritional Sciences, 2022)
Introduction:Anaemia may be a condition characterised by a decrease within the concentration of haemoglobin in the blood that results from a reduced quality or amount of red blood cells that reduce Oxygen carrying capability to tissues. Red blood cells carry haemoglobin, an iron-rich protein that attaches to oxygen in the lungs and carries it to tissues throughout the body. Anaemia occurs when you do not have enough red blood cells or when your red blood cells do not function properly. It is diagnosed when a blood test shows a haemoglobin value of less than 13.5 gm/dl in a man or less than 12.0 gm/dl in a woman. Normal values for children vary with age. Aim:To Study the current steps and practices on prevalence of anaemia among adolescents students studying in Telangana Social Welfare Residential Educational Institutions Society by different stakeholders perspective in Telangana state.Objectives:To Study the prevalence of anaemia among adolescent children’s in Telangana Social Welfare Residential Educational Institutions society by different stakeholders. To know certain measures and techniques in the study To analyse the current situation with the help of tools and techniques